2020
DOI: 10.3390/jcm9113765
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response to Gabapentin in Neuropathic Ocular Pain Associated with Dry Eye

Abstract: Purpose: To investigate the response to gabapentin treatment in patients with dry eye (DE) accompanied by features of neuropathic ocular pain (NOP), and to analyze the differences between clinical manifestations of the groups according to treatment response. Methods: We retrospectively reviewed the records of 35 patients with DE accompanied by NOP features and obtained information on their medical history and previous ocular history. The patients underwent clinical examinations of the tear film, ocular surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, the exact mechanism through which GBT, by involving multiple players, exerts its analgesic effect is complex and not definitively clarified ( Taylor and Harris, 2020 ). In ocular neuropathies, systemic administration of GBT or its analog pregabalin has been demonstrated to reduce pain ( Lichtinger et al, 2011 ; Pakravan et al, 2012 ; Wei et al, 2015 ; Ongun and Ongun, 2019 ; Yoon et al, 2020 ), although its efficacy in counteracting ocular pain in patients with DED has been questioned ( Ozmen, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanism through which GBT, by involving multiple players, exerts its analgesic effect is complex and not definitively clarified ( Taylor and Harris, 2020 ). In ocular neuropathies, systemic administration of GBT or its analog pregabalin has been demonstrated to reduce pain ( Lichtinger et al, 2011 ; Pakravan et al, 2012 ; Wei et al, 2015 ; Ongun and Ongun, 2019 ; Yoon et al, 2020 ), although its efficacy in counteracting ocular pain in patients with DED has been questioned ( Ozmen, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic drugs include gabapentin (GBT), a structural analog of gamma-amino butyric acid that has been introduced as an adjunctive therapy in epilepsy and is presently widely used to treat several kinds of neuropathic pain. The possibility that GBT may counteract ocular pain has been suggested by several studies ( Lichtinger et al, 2011 ; Pakravan et al, 2012 ; Wei et al, 2015 ; Ongun and Ongun, 2019 ; Yoon et al, 2020 ), since the first demonstration of systemic GBT efficacy in providing significant pain relief in glaucomatous patients ( Kavalieratos and Dimou, 2008 ). At least some of the clinical effects of GBT are due to high affinity interactions with the α2δ1 auxiliary subunit of presynaptic voltage-gated calcium channels ( Taylor and Harris, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these topical treatments appear to have limitations in producing an improvement in the corneal nerve morphologic status and central sensitization in patients with chronic NOP. Current systemic medication mainly includes oral antidepressants, anticonvulsants, or gabapentinoid; however, these systemic treatments have several limitations, such as delayed onset, variable efficacy, and unacceptable side effects [ 4 , 13 , 14 ]. In addition, limited data are available to support the use of systemic neuropathic pain medications for NOP associated with DE [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the wiping of C3 was more comfortable for patients than conventional instillation of eye drops, and produced a painless cooling sensation lasting approximately 40 min [ 9 ]. The OPAS scores also decreased at 1 week after treatment, indicating that the topical drug produces effect faster than systemic drugs do [ 14 ]. Moreover, although the effect was temporary, C3 was particularly effective when the patients experienced severe pain due to DE, such as when driving or sleeping, thereby resulting in an improved QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of "neuropathic corneal pain" (NCP), increasingly investigated in the past 20 years in clinical research [4,14], has been suggested to play a central role in those cases. NCP represents a current clinical challenge, as those patients are commonly not responding to classic dry eye treatments [15], and the ocular pathology is often associated with depressive disorders [16].…”
Section: Introductionmentioning
confidence: 99%